Sunlight and Protection Against Influenza - David Slusky; Richard J. Zeckhauser (Institute of Labor Economics (IZA), 2020)
Recent medical literature suggests that vitamin D supplementation protects against acute respiratory tract infection. Humans exposed to sunlight produce vitamin D directly. This paper investigates how differences in sunlight, as measured over several years across states and during the same calendar week, affect influenza incidence. We find that sunlight strongly protects against getting influenza. This relationship is driven almost entirely by the severe H1N1 epidemic in fall 2009. A 10% increase in relative sunlight decreases the influenza index in September or October by 1.1 points on a 10-point scale. A second, complementary study employs a separate data set to study flu incidence in counties in New York State. The results are strongly in accord.
Keywords: I10; I12; I18; Q5; N32; 330; Seasonal Influenza; sunlight; vitamin d; natural experiment; H1N1